2019
DOI: 10.1186/s12894-019-0494-0
|View full text |Cite
|
Sign up to set email alerts
|

Testicular cancer in Geneva, Switzerland, 1970–2012: incidence trends, survival and risk of second cancer

Abstract: Background This paper describes the testicular cancer trends for incidence, survival, socio-economic status (SES) disparities and second cancer occurrence in Geneva, Switzerland, a high-risk population. Methods We included all testicular germ-cell tumors recorded in the population-based Geneva cancer registry during the period 1970–2012. Changes in incidence trends were assessed using Joinpoint regression to calculate the annual percentage change (APC). Overall and canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
3
3
0
Order By: Relevance
“…In further stratification analysis by different age groups, the older the TC were getting diagnosed, the higher the proportion of death from heart diseases occurred. This finding is in line with the study of Chunkit Fung et al [ 10 ] and they also got a powerful conclusion that increased mortality for heart diseases after chemotherapy was confined to the first year after TC diagnosis and older age at diagnosis was independent risk factors. Besides, in patients diagnosed with TC within 1 years, deaths due to cerebrovascular diseases were associated with significantly higher risks compared with the general population (SMR, 2.73; 95%CI, 1.18–5.37), which was in agreement with the study by Chunkit Fung et al [ 10 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In further stratification analysis by different age groups, the older the TC were getting diagnosed, the higher the proportion of death from heart diseases occurred. This finding is in line with the study of Chunkit Fung et al [ 10 ] and they also got a powerful conclusion that increased mortality for heart diseases after chemotherapy was confined to the first year after TC diagnosis and older age at diagnosis was independent risk factors. Besides, in patients diagnosed with TC within 1 years, deaths due to cerebrovascular diseases were associated with significantly higher risks compared with the general population (SMR, 2.73; 95%CI, 1.18–5.37), which was in agreement with the study by Chunkit Fung et al [ 10 ].…”
Section: Discussionsupporting
confidence: 90%
“…This finding is in line with the study of Chunkit Fung et al [ 10 ] and they also got a powerful conclusion that increased mortality for heart diseases after chemotherapy was confined to the first year after TC diagnosis and older age at diagnosis was independent risk factors. Besides, in patients diagnosed with TC within 1 years, deaths due to cerebrovascular diseases were associated with significantly higher risks compared with the general population (SMR, 2.73; 95%CI, 1.18–5.37), which was in agreement with the study by Chunkit Fung et al [ 10 ]. And they also reported that cerebrovascular disease mortality with significantly elevated risks after chemotherapy but not surgery alone [ 10 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In testicular cancers, which are the most common malignant disease in men between 14-44 years of age [59,60], with a peak incidence at 30-34 years of age [61,62], a sudden increase in the number of patients half a century ago was recorded [63,64], which was equally influenced by hereditary factors and environmental conditions [59]. Developed countries such as New Zealand [65], Norway [66], Canada [67], Denmark [68], Great Britain [69], Israel [70], Czech Republic [71], Australia [72], Croatia [73], the USA [74], France [62], Germany [75], and Switzerland [76], saw a significant increase in testicular cancer. According to [77,78], this type of cancer affects the populations of Europe and Australia the most, and Asia and Africa the least.…”
Section: Testicular Cancermentioning
confidence: 99%
“…There are two main types of TGCT: seminoma and non-seminoma, where the non-seminoma tumours are identified according to what type of cells they are made of. With effective treatment, the overall five-year survival rate is 97% (Baird et al 2018 ), although the treatment can cause impairment of spermatogenesis and also lead to secondary cancers (Parekh et al 2020 ; Schaffar et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%